The Demand for Money, Financial Innovation, and the Welfare Cost of Inflation: An Analysis with Household Data - Attanasio, Orazio P.; Guiso, Luigi; Jappelli, Tullio (Journal of Political Economy, 2002)
We use microeconomic data on households to estimate the parameters of the demand for currency derived from a generalized Baumol‐Tobin model. Our data set contains information on average currency, deposits, and other interest‐bearing assets; the number of trips to the bank; the size of withdrawals; and ownership and use of ATM cards. We model the demand for currency accounting for adoption of new transaction technologies and the decision to hold interest‐bearing assets. The interest rate and expenditure flow elasticities of the demand for currency are close to the theoretical values implied by standard inventory models. However, we find significant differences between individuals with an ATM card and those without. The estimates of the demand for currency allow us to calculate a measure of the welfare cost of inflation analogous to Bailey’s triangle, but based on a rigorous microeconometric framework. The welfare cost of inflation varies considerably within the population but never turns out to be very large (about 0.1 percent of consumption or less). Our results are robust to various changes in the econometric specification. In addition to the main results based on the average stock of currency, the model receives further support from the analysis of the number of trips to and average withdrawals from the bank and the ATM.